Associations between Apolipoprotein E Gene Polymorphism, Diet and Dyslipidemia in a Yao Minority Area, China. Issue 7 (3rd October 2022) - Cai, Jiansheng; Liu, Qiumei; Liu, Shuzhen; Mai, Tingyu; Xu, Min; He, Haoyu; Mo, Chunbao; Xu, Xia; Zhang, Junling; Tang, Xu; Lu, Huaxiang; Li, You; et al.
Abstract: Objective: This study aimed to assess the effects of Apolipoprotein E ( APOE ) gene polymorphisms, dietary nutrient intake, and their interactions on the prevalence of dyslipidemia in a Yao minority area, China. Methods: rs429358, rs7412, rs7259620, and rs405509 of the APOE gene were genotyped in 1014 adults aged ≥30 years by using the MassArray system. Dietary nutrients intake data were ascertained from a 109-item food frequency questionnaire (FFQ). Results: Multifactorial logistics regression analysis showed that dyslipidemia was associated with rs7412-CT/TT genotype (OR: 0.540, Bonferroni correction confidence interval: 0.336–0.869), high fat intake (OR: 1.644, 95% CI: 1.128–2.395), high saturated fatty acid (SFA) intake (OR: 1.668, 95% CI: 1.146–2.428), medium carbohydrate intake (OR: 0.634, 95% CI: 0.461–0.873) and high carbohydrate intake (OR: 0.591, 95% CI: 0.406–0.858). The results of logistics regression multiplication model showed that medium carbohydrate intake in the carriers of the rs7412 minor alleles was associated with a low risk of dyslipidemia (OR: 0.433, Bonferroni correction confidence interval: 0.199–0.941). Conclusions: Genetic variations at the rs7412, dietary fat, SFA, and carbohydrate intake and the interaction between APOE gene polymorphisms and carbohydrate intake are associated with dyslipidemia in Yao nationality people.